Hubungan Repetitive Motion, Beban Kerja, Shift Kerja, dan Kualitas Tidur dengan Kelelahan Kerja pada Petugas Aviation Security - Sari, Cindy Puspita; Sulistyorini, Anita; Marji, Marji; Fanani, Erianto; Tama, Tika Dwi (National Journal of Occupational Health and Safety, 2025)
The aviation sector is one of the work areas that requires the implementation of Occupational Health and Safety (OHS). Work in the aviation sector also presents various risks, one of which can occur in work accidents caused by fatigue. Based on preliminary studies conducted on Aviation Security Officers (AVSEC), there are symptoms of work fatigue. The study aims to determine the relationship of repetitive motion, workload, work shifts, and sleep quality with job fatigue in AVSEC officers. The research used a quantitative observational study with an analytic design through a cross-sectional approach with a total of 76 AVSEC officers. The instruments are stopwatch to measure repetitive motion, NASA-TLX questionnaire to measure the level mental workload, pulse oximeter to determine physical workload, PSQI questionnaire to determine sleep quality, and IFRC questionnaire to determine work fatigue. Data analyzed using Spearman's rank test and ordinal logistic regression test. The results show a significant relationship between all independent variables, namely repetitive motion (p-value <0.001), mental workload (p value <0.001), physical workload (p value = 0.041), work shift (p value = 0.002), and sleep quality (p value <0.001) with job fatigue. The most related variable in this study with work fatigue variable is mental workload variable (p-value = 0.002).